Pengadaan Tempat Sampah Organik dan Anorganik Sebagai Wujud Implementasi Pemilahanm Sampah di Desa Pasinan, Kecamatan Lekok, Kabupaten Pasuruan - Khairunnisa Salsabila Putri Prameswari; Rafida Febriana Widya Putri; Abdullah Ilmi; Mila Hariani; Rahayu Mardikaningsih; Didit Darmawan; Moh. Djaelani; Cilda Thesisa Ilmawan Dzinnur (FKIP, Universitas Palangka Raya, 2024)
Limitations in the provision of rubbish bins in Pasinan Village, Lekok District, Pasuruan Regency have become one of the problems that needs to be immediately evaluated to prevent the emergence of diseases that could endanger public health. The aim of implementing to find a solution to the environmental pollution problem currently faced by the people of Pasinan Village, Lekok District, Pasuruan Regency. As a solution, a Trash Can Procurement program was held as a step to reduce the dirty environment in the village. This report will explain the role of trash cans in increasing public awareness of the importance of environmental cleanliness and understanding of sorting organic and inorganic waste. The trash cans were handed over directly to the relevant parties. The community welcomed this activity well and enthusiastically, considering it an important step in improving environmental cleanliness in Pasinan Village, Lekok District, Pasuruan Regency. Overall, this activity is considered effective in overcoming the waste problem, so that Pasinan Village can become a cleaner and healthier village.